Gall inducing arthropods from a seasonally dry tropical forest in Serra do Cipo, Brazil - Coelho, MS; Almada, ED; Fernandes, G W; Carneiro, MAA; dos Santos, RM; Quintino, A V; Sanchez-Azofeifa, A (Revista brasileira de entomologia, 2009)
Gall inducing arthropods from a seasonally dry tropical forest in Serra do Cipo, Brazil. Highly diverse forms of galling arthropods can be identified in much of southeastern Brazil's vegetation. Three fragments of a Seasonally Dry Tropical Forest (SDTF) located in the southern range of the Espinhaco Mountains were selected for study in the first survey of galling organisms in such tropical vegetation. Investigators found 92 distinct gall morphotypes on several organs of 51 host plant species of 19 families. Cecidomyiidae (Diptera) was the most prolific gall-inducing species, responsible for the largest proportion of galls (77%) observed. Leaves were the most frequently galled plant organ (63%), while the most common gall morphotype was of a spherical shape (30%). The two plant species, Baccharis dracunculifolia (Asteraceae) and Celtis brasiliensis (Cannabaceae), presented the highest number of gall morphtypes, displaying an average of 5 gall morphotypes each. This is the first study of gall-inducing arthropods and their host plant species ever undertaken in a Brazilian SDTF ecosystem. Given the intense human pressure on SDTFs, the high richness of galling arthropods, and implied floral host diversity found in this study indicates the need for an increased effort to catalogue the corresponding flora and fauna, observe their intricate associations and further understand the implications of such rich diversity in these stressed and vulnerable ecosystems.